2014
DOI: 10.9775/kvfd.2013.10521
|View full text |Cite
|
Sign up to set email alerts
|

Bütil Hidroksitoluen Tarafından Mikronükleus İndüksiyonunun Wistar Sıçan Kemik İliği Hücrelerinde Araştırılması

Abstract: SummaryThis study aims to investigate whether Butylated Hydroxytoluene (BHT), the synthetic antioxidant and food additive, increases the frequency of micronucleated polychromatic erythrocytes (MNPCEs) in rat bone marrow. BHT, dissolved in corn oil, was administered intraperitoneally to 8-10 week old male and female Wistar rats (n=36) in three different doses (125, 250 and 500 mg/kg b.w.) for two different time periods. 12-and 24-h after BHT treatment, the bone marrow samples were analyzed for the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to Llana-Ruiz-Cabello et al (2018), micronucleus assay was applied to evaluate genotoxic effect of oregano essential oil orally administrated to rats and the results showed that PCE/total erythrocytes ratio exhibited significantly different values compared to control. Polat et al (2014) reported that consumption of Butylated hydroxytoluene (BHT) had a cytotoxic effect on bone marrow and the PCE/NCE ratio decreased in all applied BHT doses.…”
Section: ) Genotoxic Effects and Liver Toxicity In Swiss Albino Mice Males After Acute And Chronic Exposure Of Diacetyl And Butter Flavormentioning
confidence: 99%
“…According to Llana-Ruiz-Cabello et al (2018), micronucleus assay was applied to evaluate genotoxic effect of oregano essential oil orally administrated to rats and the results showed that PCE/total erythrocytes ratio exhibited significantly different values compared to control. Polat et al (2014) reported that consumption of Butylated hydroxytoluene (BHT) had a cytotoxic effect on bone marrow and the PCE/NCE ratio decreased in all applied BHT doses.…”
Section: ) Genotoxic Effects and Liver Toxicity In Swiss Albino Mice Males After Acute And Chronic Exposure Of Diacetyl And Butter Flavormentioning
confidence: 99%